A Subset of CXCR5+CD8+ T Cells in the Germinal Centers From Human Tonsils and Lymph Nodes Help B Cells Produce Immunoglobulins - Shen, Juan; Luo, Xi; Wu, Qiongli; Huang, Jun; Xiao, Guanying; Wang, Liantang; Yang, Binyan; Li, Huabin; Wu, Changyou (Frontiers in Immunology, 2018)
Recent studies indicated that CXCR5+CD8+ T cells in lymph nodes could eradicate virus-infected target cells. However, in the current study we found that a subset of CXCR5+CD8+ T cells in the germinal centers from human tonsils or lymph nodes are predominately memory cells that express CD45RO and CD27. The involvement of CXCR5+CD8+ T cells in humoral immune responses is suggested by their localization in B cell follicles and by the concomitant expression of costimulatory molecules, including CD40L and ICOS after activation. In addition, CXCR5+CD8+ memory T cells produced significantly higher levels of IL-21, IFN-γ and IL-4 at mRNA and protein levels compared to CXCR5-CD8+ memory T cells, but IL-21-expressing CXCR5+CD8+ T cells did not express Granzyme B and perforin. When cocultured with sorted B cells, sorted CXCR5+CD8+ T cells promoted the production of antibodies compared to sorted CXCR5-CD8+ T cells. However, fixed CD8+ T cells failed to help B cells and the neutralyzing antibodies against IL-21 or CD40L inhibited the promoting effects of sorted CXCR5+CD8+ T cells on B cells for the production of antibodies. Finally, we found that in the germinal centers of lymph nodes from HIV-infected patients contained more CXCR5+CD8+ T cells compared to normal lymph nodes. Due to their versatile functional capacities, CXCR5+CD8+ T cells are promising candidate cells for immune therapies, particularly when CD4+ T cell help are limited.